Numerical study on fatigue behavior of tubular joints for signal support structures. (April 2018) - Wang, Zongyi; Zhang, Yunfeng; Wang, Yuanqing; Du, Xinxi; Yuan, Huanxin
Abstract: Welded tubular joints are widely used for the mast arm pole connection in signal support structures. In order to study the fatigue behavior of such welded tubular joints, static loading and fatigue tests were carried out on several full-scale experiments. In order to understand the local behavior and perform parametric study of critical factors such as initial crack location, finite element (FE) models are subsequently built and the numerical simulation results are validated with the experimental test results. Stress intensity factors (SIFs) at the deepest point of fatigue cracks are calculated by the FE method and an empirical equation are examined by comparison. It is found that the numerical simulation results are in good agreement with the experimental test results. The effect of initial crack location on the SIF and the fatigue life are also investigated. The Bowness equation will result in higher SIF value and more conservative fatigue life prediction for the concerned welded tubular joints. The SIFs at the deepest point decrease and fatigue life increases with the increasing initial crack angle. Highlights: The FEA results agree well with the experimental test results for the static loading model and the fatigue loading model. The Bowness equation will produce higher SIF results and more conservative fatigue life prediction for weld-to-transverse end plate joints. The SIFs at the deepest point decrease and the fatigue lives increase with the increasing initial crack angle.